Achieving service-oriented architecture : applying an enterprise architecture approach - Sweeney, Rick (Hoboken, N.J. : Wiley, 2010)
Presents a comprehensive methodology and framework for adopting and managing a successful service oriented architecture environment. This book focuses on setting up an enterprise architecture practice for service-oriented architecture. It discusses the implementation and governance processes for SOA.
Includes index.
oif 23/06/15
Loan
Keywords: Information technology-management; Management information systems; Service-oriented architecture (Computer science)